2004
DOI: 10.1101/lm.75604
|View full text |Cite
|
Sign up to set email alerts
|

Reverberation, storage, and postsynaptic propagation of memories during sleep

Abstract: In mammals and birds, long episodes of nondreaming sleep ("slow-wave" sleep, SW) are followed by short episodes of dreaming sleep ("rapid-eye-movement" sleep, REM). Both SW and REM sleep have been shown to be important for the consolidation of newly acquired memories, but the underlying mechanisms remain elusive. Here we review electrophysiological and molecular data suggesting that SW and REM sleep play distinct and complementary roles on memory consolidation: While postacquisition neuronal reverberation depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 167 publications
10
88
2
Order By: Relevance
“…This observation constitutes, to our knowledge, the first electrophysiological observation of such a long lasting activation of burst firing which may underlie the increase in dopamine levels reported during various behaviors such as feeding, reward, punishment, or sex (Schultz, 2002). The similarity between dopaminergic activity observed during PS and food consumption suggests that, even if sensory thresholds were high and the animal was not perceiving external stimuli, neuronal reactivations occurring during PS, throughout the brain (Louie and Wilson, 2001;Maquet et al, 2000;Peigneux et al, 2003;Ribeiro and Nicolelis, 2004), could underlie the perception of internally generated rewarding or at least salient experiences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This observation constitutes, to our knowledge, the first electrophysiological observation of such a long lasting activation of burst firing which may underlie the increase in dopamine levels reported during various behaviors such as feeding, reward, punishment, or sex (Schultz, 2002). The similarity between dopaminergic activity observed during PS and food consumption suggests that, even if sensory thresholds were high and the animal was not perceiving external stimuli, neuronal reactivations occurring during PS, throughout the brain (Louie and Wilson, 2001;Maquet et al, 2000;Peigneux et al, 2003;Ribeiro and Nicolelis, 2004), could underlie the perception of internally generated rewarding or at least salient experiences.…”
Section: Discussionmentioning
confidence: 98%
“…During the past 50 years of sleep research, PS has been associated with various functions, ranging from corneal respiration (Fitt and Gonzalez, 2006) to dreaming (Aserinsky and Kleitman, 1953). It has been proposed recently that one possible function of PS is to participate in reconsolidation of newly acquired memories during sleep via off-line replay of previously experienced events (Ribeiro and Nicolelis, 2004;Stickgold et al, 2001;Stickgold and Walker, 2005). Indeed, in humans, imaging studies showed that cerebral regions activated during learning are reactivated again during PS following the task (Maquet et al, 2000;Peigneux et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Candidate mechanisms supporting memory consolidation during REM sleep possibly involve increased protein synthesis and plasticity-related gene expression during this sleep stage. Whereas non-REM sleep is characterized by diminished activity of such genes and a greatly reduced ability to induce synaptic long-term potentiation, REM sleep provides a more adequate milieu of neurotransmitters and modulators for synaptic plastic changes (Ribeiro and Nicolelis, 2004;Bramham and Srebro, 1989). Ribeiro et al (Ribeiro et al, 1999 revealed an increased expression of the immediate early genes arc and zif-268 during REM sleep after induction of long-term potentiation during prior wakefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple brain areas (e.g., hippocampus, amygdala, cerebral cortex, striatum, cerebellum) seem to be involved in these processes (Attwell et al, 2002;Ribeiro and Nicolelis, 2004;Kassardjian et al, 2005;Ji and Wilson, 2007;Montgomery and Buzsáki, 2007;Karlsson and Frank, 2009). For example, similar cell ensembles in the amygdala of transgenic mice were found to be active during learning and retrieval of fear memory (Reijmers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%